Utility of spatial description for evaluation of prosumption effects on examples of IT companies - Stępniak, Cezary (Użyteczność deskrypcji przestrzennej do oceny efektów prosumpcji na przykładzie firm informatycznych, 2018)
This article proposes concepts for a tool to support the management of prosumer activity. Using spatial descriptions, it allows for multi-criteria visualization of the effects of prosumer activity. Spatial description is a way of mapping reality using the broadly understood concept of space. In this case, space can be seen not only in geographic dimensions, but also as heuristic or mathematical space. The study presents the principles of construction, operation and objectives of using the proposed tool. The practical application of the tool to assess the prosumption effects of an IT company dealing with the implementation of ERP / BI class information systems has been shown. The applicability of the proposed tool has been verified on the basis of two criteria: feasibility and usability.. The article shows what can be visualized and in what way, and what benefits it can bring. The indication of how the concept of space can be used in dynamic management
Informatyka Ekonomiczna = Business Informatics, 2018, Nr 3 (49), s. 89-105
Keywords: prosumption effects; ERP application effects; spatial description; map of prosumption effects; efekty prosumpcji; deskrypcja przestrzenna; mapy efektów prosumpcji; efekty wdrażania systemów ERP